Tetraalkylammonium salt as photoinitiator of vinyl polymerization in organic and aqueous media: A mechanistic and laser flash photolysis study - Gomez, María Lorena (2002)
N-Dimethyl-N-[2-(N,N-dimethylamino)ethyl]-N-(1-methylnaphthyl)ammonium tetrafluoroborate (I) was synthesized with the aim of obtaining a versatile photoinitiator for vinyl polymerization in organic solvents and water. Salt I was able to trigger the polymerization of acrylamide, 2-hydroxyethylmethacrylate and styrene even at very low concentrations of the salt (∼1.0 × 10-5 M). Using laser flash photolysis and fluorescence techniques and analyzing the photoproduct distribution, we were able to postulate a mechanism for the photodecomposition of the salt. With irradiation, I undergoes an intramolecular electron-transfer reaction to form a radical ion pair (RIP). The RIP intermediate decomposes into free radicals. The RIP and the free radicals are active species for initiating the polymerization. Depending on the concentration of the vinyl monomers studied, the initiation mechanism of the polymerization reaction changes. At large monomer concentrations, the RIP state is postulated to trigger the reaction by generating the anion radical of the olefin substrate. At a low monomer concentration, the free radicals produced by the decomposition of I are believed to start the chain reaction.